2012
DOI: 10.1371/journal.pone.0040943
|View full text |Cite
|
Sign up to set email alerts
|

ATRA Inhibits the Proliferation of DU145 Prostate Cancer Cells through Reducing the Methylation Level of HOXB13 Gene

Abstract: All-trans retinoic acid (ATRA) has been widely investigated for treatments of many cancers including prostate cancer. HOXB13, silenced in androgen receptor-negative (AR−) prostate cancer cells, plays a role in AR− prostate cancer cell growth arrest. In this study we intended to elucidate the mechanisms that are involved in the proliferation inhibition of AR− prostate cancer cells triggered by ATRA. We discovered that ATRA was able to induce the growth arrest and to increase HOXB13 expression in AR− prostate ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 47 publications
(85 reference statements)
4
20
0
Order By: Relevance
“…A compound such as DZNep decreases H3K27me3 and H3K9me2 repressive methylation mediated by EZH2 as well as the active histone mark H3K4me3 and H3K36me3, therefore preventing a broad epigenetic resetting of the tumor cells (49). Noteworthy, all-trans retinoid acid (ATRA), which is the only chemical drug in clinical use for tumor cell differentiation and is an inhibitor of ALDH activity, was recently shown to reduce the proliferation of prostate cancer DU145 cells through downregulation of EZH2-mediated methylation of the HOXB13 gene, which encodes Hoxb13 antiproliferative transcription factor (50). Several studies have demonstrated that the level of EZH2 expression is positively correlated with prostate cancer aggressiveness, and EZH2 is not only overexpressed in metastatic prostate cancer but also in the localized cancers with a high risk of recurrence after radical prostatectomy (22,46,51,52).…”
Section: Discussionmentioning
confidence: 99%
“…A compound such as DZNep decreases H3K27me3 and H3K9me2 repressive methylation mediated by EZH2 as well as the active histone mark H3K4me3 and H3K36me3, therefore preventing a broad epigenetic resetting of the tumor cells (49). Noteworthy, all-trans retinoid acid (ATRA), which is the only chemical drug in clinical use for tumor cell differentiation and is an inhibitor of ALDH activity, was recently shown to reduce the proliferation of prostate cancer DU145 cells through downregulation of EZH2-mediated methylation of the HOXB13 gene, which encodes Hoxb13 antiproliferative transcription factor (50). Several studies have demonstrated that the level of EZH2 expression is positively correlated with prostate cancer aggressiveness, and EZH2 is not only overexpressed in metastatic prostate cancer but also in the localized cancers with a high risk of recurrence after radical prostatectomy (22,46,51,52).…”
Section: Discussionmentioning
confidence: 99%
“…This finding provided a mechanistic link to PL3’s previously known anti-inflammatory and cytotoxic activities in other cancer types including breast cancer and hepatocellular carcinoma (Chang et al, 2006), and offers an insightful approach to molecularly target EZH2. Additionally, a well-known anticancer agent, all-trans retinoic acid (ATRA), whose apoptosis- inducing activity has been investigated in leukemia (Drach et al, 1993; Hagiwara et al, 2010), gastric cancer (Hoang et al, 2010) and prostate cancer (Zhang, 2002), is recently evidenced to function through repression of EZH2- and DNMT3B-mediated hypermethylation of HOXB13, a member of the homeobox superfamily and an anti-proliferative transcription factor (Liu et al, 2012). EZH2 is known to recruit DNMT3B to promoter regions of specific gene loci since the latter does not inherently have DNA-binding domains and depends on EZH2’s presence in order to carry out DNA methylation (Vire et al, 2006).…”
Section: Pharmacological Targeting Of Ezh2mentioning
confidence: 99%
“…EZH2 is known to recruit DNMT3B to promoter regions of specific gene loci since the latter does not inherently have DNA-binding domains and depends on EZH2’s presence in order to carry out DNA methylation (Vire et al, 2006). Upon ATRA treatment, cell growth arrest was observed in androgen-independent prostate cancer DU145 cells, following the marked downregulation of both EZH2 and DNMT3B, as well as reduced methylation and restored expression level of HOXB13 (Liu et al, 2012). …”
Section: Pharmacological Targeting Of Ezh2mentioning
confidence: 99%
“…However, administration of the histone deacetylase inhibitor sodium butyrate suppressed repressive histone modifications and resulted in a dramatic increase in HOXB13 and concomitant inhibition of cell proliferation 64. Liu et al65 noted a similar effect in which all-trans retinoic acid increased HOXB13 expression and decreased cell growth via histone methylation modifications mediated by EZH2 and DNMT3b.…”
Section: Hoxb13 and Prostate Cancermentioning
confidence: 99%